2015
DOI: 10.1166/jnn.2015.9734
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Applications of Nanodiamonds: An Overview

Abstract: Nanodiamonds are a novel class of nanomaterials which have raised much attention for application in biomedical field, as they combine the possibility of being produced on large scale using relatively inexpensive synthetic processes, of being fluorescent as a consequence of the presence of nitrogen vacancies, of having their surfaces functionalized, and of having good biocompatibility. Among other applications, we mainly focus on drug delivery, including cell interaction, targeting, cancer therapy, gene and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 69 publications
(100 reference statements)
0
46
0
Order By: Relevance
“…[1][2][3][4] In recent years, significant amount of research has been conducted to harness the excellent mechanical and biological properties of carbon-based nano-particles. Graphene oxide [5][6][7] , carbon nanotubes [8][9][10] and nanodiamonds [11][12][13][14] have been studied for possible applications in dentistry as well as medicine. Nanodiamonds (NDs) were first developed by scientists in the USSR during the 1960s and revealed to the public during the mid '80s.…”
Section: Accepted Version Science Of Advanced Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3][4] In recent years, significant amount of research has been conducted to harness the excellent mechanical and biological properties of carbon-based nano-particles. Graphene oxide [5][6][7] , carbon nanotubes [8][9][10] and nanodiamonds [11][12][13][14] have been studied for possible applications in dentistry as well as medicine. Nanodiamonds (NDs) were first developed by scientists in the USSR during the 1960s and revealed to the public during the mid '80s.…”
Section: Accepted Version Science Of Advanced Materialsmentioning
confidence: 99%
“…15 NDs can be synthesized via detonation, chemical vapors deposition, ultrasonic cavitation, irradiation with pulsed lasers and application of high temperature / high pressure (HTHP). 12,[15][16][17] As shown in Figure 1, apart from the route of synthesis, NDs are also classified according to their size: nanocrystalline particles (1 to150 nm), ultra-nanocrystalline particles (2 to 10 nm), and diamondoids (1 to 2 nm). 15,18 A schematic diagram of a nanodiamond crystal is shown in Figure 2.…”
Section: Accepted Version Science Of Advanced Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…54 Diamond nanoparticles also used as an important therapeutic tool in tumor patches and wound healing. 108 Fullerene has uniquely identified a class of carbon allotropes which described as 60 linked carbon with 60 vertices and 32 faces. 109 The extensive research on nanosized C60 have identified its use in drug delivery.…”
mentioning
confidence: 99%